Performance of Azadirachta Indica as Bio-Flocculant in Reducing Turbidity Concentration from Landfill Leachate - Zakaria, Siti Nor Farhana (International Journal of Integrated Engineering, 2025)
It is widely established that the amount of municipal solid debris produced daily continues to rise. As a result, municipal solid waste (MSW) landfills struggle with leachate formation, which puts groundwater and surface water at serious risk. Leachate is a liquid that has extracted dissolved and suspended materials from waste and travels through landfills. Dumping landfill leachate directly into a body of water or the environment puts the ecology and public health in danger since it contains high levels of COD, pH, ammonia nitrogen, turbidity, and heavy metals. Therefore, finding and offering an efficient landfill leachate treatment is undoubtedly required. The purpose of this study is to evaluate the performance of the bio-flocculant Azadirachta Indica (bf-Ai) as a flocculant in the coagulation-flocculation process for the treatment of landfill leachate under various experimental circumstances. Additionally, the performance of conventional coagulant alone, which is alum, will be experimented and compared with a combination of alum (as coagulant) and Azadirachta Indica (Ai) as bio-flocculant (alum + bf-Ai). Based on this study, the combination of alum + bf-Ai recorded higher removal of turbidity, which is 64% compared to alum alone (62%) at raw pH of leachate and the dosage of alum + bf-Ai as 0.8g and 5g, respectively. Additionally, reduction in the usage of alum dosage can also be seen in this combination, which decreases from 1.4g to 0.8g only. This reduction is a positive sign since alum alone has produced hazardous sludge (secondary pollutants) damaging the environment and human health. Thus, further research should be conducted on the potential of Ai as a bio-flocculant aid.